Probing the Rotation Curve of NGC 4501 Galaxy using Two Different Models - Ali, Israa Abdulqasim Mohammed; Mahdi, Hareth Saad; Zainal Abidin, Zamri; Lee, Danial Ahmad Ariffin (Malaysian Journal of Science, 2025)
Rotation curves of spiral galaxies have become an important tool for investigating their physical properties and is usually used as evidence for dark matter presence in their haloes. This research aims to probe the rotation curve of the spiral galaxy NGC 4501. The HI data of this galaxy have been collected from Very Large Array (VLA) and nonlinear fitting techniques have been used in this research for different components: stars, gas and halo. Particularly, kinematic analysis of NGC 4501’s rotation curve has been carried out in this research using two different profile models: pseudo-isothermal profile and the Moore profile. The results of this study clearly showed that pseudo-isothermal model is better at reproducing the rotation curve of NGC 4501 than Moore model. The reduced chi-square, χ_"red " ^2 of pseudo-isothermal is found to be close to one whereas Moore model does not agree with observational data. This is due to the fact that the pseudo-isothermal model is characterized primarily by the linearity of its behavior within the inner region together with the flat profile at large radii. As a result, the dark matter distribution in NGC 4501 is one that may be represented by a core halo model.